Three-dimensional printing in healthcare - Pérez Sanpablo, Alberto Isaac; Romero Avila, Elisa; González Mendoza, Arturo (Revista Mexicana de Ingenieria Biomedica, 2021)
This work aims to briefly present the cutting edge of 3D printing innovation in healthcare. This technology is used for surgical planning, medical education, bioprinting of tissues, and medical equipment spare parts in fields like pharmacology, prosthetics, surgery, and regenerative medicine. A review of the last decade was made in the search engines of PubMed and Espacenet. Three authors reviewed titles, abstracts, and keywords separately to identify studies appropriate to the topic. After the initial examination, complete texts of identified relevant studies were obtained and classified according to the authors. Results were synthesized in a narrative literature review. The revision showed that 3D printing has become of common use in the healthcare system since it allows medical personnel to implement customized solutions for each patient, thus reducing the probability of a false diagnostic or treatment. Major applications among the advantages and disadvantages of 3D printing in healthcare were presented. Nowadays, the main challenge in 3D printing is the cost of the equipment and its manufacturing. In the future, the challenges in cost could be reduced, but processing requirements and limited materials may still need further work.